2020
DOI: 10.1002/hep4.1574
|View full text |Cite
|
Sign up to set email alerts
|

Nonfasted Liver Stiffness Correlates with Liver Disease Parameters and Portal Hypertension in Pediatric Cholestatic Liver Disease

Abstract: Elastographic measurement of liver stiffness is of growing importance in the assessment of liver disease. Pediatric experiences with this technique are primarily single center and limited in scope. The Childhood Liver Disease Research Network provided a unique opportunity to assess elastography in a well‐characterized multi‐institutional cohort. Children with biliary atresia (BA), alpha‐1 antitrypsin deficiency (A1ATD), or Alagille syndrome (ALGS) followed in a prospective longitudinal network study were eligi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 21 publications
(28 reference statements)
0
18
0
2
Order By: Relevance
“…Dabei istbesonders auf sonographischeIndikatoren einer sich entwickelnden portalen Hypertension zu achten (zunehmende Milzgröße, Rarefizierung intrahepatischer Portaläste, Reduktion oder gar Umkehr des portalen Blutflusses in der Dopplersonographie). Die Leberelastographie kann ergänzend hilfreich sein [24,25]. Spezifische sonographische Veränderungen, die auf einen Alpha-1-Antitrypsin-Mangel hinweisen, gibt es allerdings nicht.…”
Section: Sonographie Mit Elastographieunclassified
See 1 more Smart Citation
“…Dabei istbesonders auf sonographischeIndikatoren einer sich entwickelnden portalen Hypertension zu achten (zunehmende Milzgröße, Rarefizierung intrahepatischer Portaläste, Reduktion oder gar Umkehr des portalen Blutflusses in der Dopplersonographie). Die Leberelastographie kann ergänzend hilfreich sein [24,25]. Spezifische sonographische Veränderungen, die auf einen Alpha-1-Antitrypsin-Mangel hinweisen, gibt es allerdings nicht.…”
Section: Sonographie Mit Elastographieunclassified
“…B. Gerinnung, Albumin, Cholinesterase oder die Serumspiegel fettlöslicher Vitamine zu empfehlen. Neben der Sonographie zur Beurteilung des Leberparenchyms und der Dokumentation der Milzgröße sollte, wenn möglich, auch eine Leberelastographie erfolgen [25]. Bei Zunahme der Fibrose ist eine Intensivierung der Betreuung anzustreben.…”
Section: Managementunclassified
“…The study indicated a positive correlation between several biochemical indicators (total bilirubin, ALT, AST, gamma-glutamyltranspeptidase (GGT), international normalized ratio (INR), GGT to platelet ratio (GPR), AST to platelet ratio, spleen size, pediatric end-stage liver disease score, and the existence of portal hypertension. Meanwhile, the study also pointed out a more detailed correlation of LSM and portal hypertension grades, indicating the important role of LSM in classifying both the existence and degree of portal hypertension [ 23 ]. Another study published in 2020 included 140 patients with clinically significant portal hypertension (CSPH) and investigated the diagnostic performance of LSM of portal hypertension.…”
Section: Diagnosis Of Portal Hypertension Via Liver Stiffness Measure...mentioning
confidence: 99%
“…Use of FibroScan for this purpose in children with ALGS remains investigational and is not yet part of routine clinical care. 90…”
Section: Management Diagnostic Testingmentioning
confidence: 99%